The Impact of Language Opacity and Proficiency on Reading Strategies in Bilinguals: An Eye Movement Study - de León Rodríguez, Diego; Buetler, Karin A.; Eggenberger, Noëmi; Laganaro, Marina; Nyffeler, Thomas; Annoni, Jean-Marie; Müri, René M. (Frontiers in Psychology, 2016)
Reading strategies vary across languages according to orthographic depth – the complexity of the grapheme in relation to phoneme conversion rules – notably at the level of eye movement patterns. We recently demonstrated that a group of early bilinguals, who learned both languages equally under the age of seven, presented a first fixation location (FFL) closer to the beginning of words when reading in German as compared with French. Since German is known to be orthographically more transparent than French, this suggested that different strategies were being engaged depending on the orthographic depth of the used language. Opaque languages induce a global reading strategy, and transparent languages force a local/serial strategy. Thus, pseudo-words were processed using a local strategy in both languages, suggesting that the link between word forms and their lexical representation may also play a role in selecting a specific strategy. In order to test whether corresponding effects appear in late bilinguals with low proficiency in their second language (L2), we present a new study in which we recorded eye movements while two groups of late German-French and French-German bilinguals read aloud isolated French and German words and pseudo-words. Since a transparent reading strategy is local and serial, with a high number of fixations per stimuli, and the level of the bilingual participants’ L2 is low, the impact of language opacity should be observed in L1. We therefore predicted a global reading strategy if the bilinguals’ L1 was French (FFL close to the middle of the stimuli with fewer fixations per stimuli) and a local and serial reading strategy if it was German. Thus, the L2 of each group, as well as pseudo-words, should also require a local and serial reading strategy. Our results confirmed these hypotheses, suggesting that global word processing is only achieved by bilinguals with an opaque L1 when reading in an opaque language; the low level in the L2 gives way to a local and serial reading strategy. These findings stress the fact that reading behavior is influenced not only by the linguistic mode but also by top-down factors, such as readers’ proficiency.